THE EFFECT OF HEAD OF MADRASAH SUPERVISION ON TEACHER PERFORMANCE IN STANAWIYAH STATE MADRASAH IN KOLAKA DISTRICT - Kasmawati, Kasmawati; Syamsyuddin; Wahyuni (Department of Islamic Education Management, 2023)
This research was conducted with the objectives of: (1) to find out the supervision of madrasah heads in state MTs in Kolaka Regency, (2) to find out the performance of teachers in State MTs in Kolaka Regency, (3) to find out whether or not there was a significant influence between the supervision of madrasah heads on performance of teachers in state MTs in Kolaka district. This research is a quantitative research using ex post facto approach. The population in this study were all teachers at MTs Negeri 1 Kolaka and MTs Negeri 2 Kolaka, totaling 123 people so that a sample of 95 people was obtained using the cluster sampling technique. Data collection techniques used in this study were questionnaires and documentation. Data were analyzed using descriptive statistics and inferential statistics. The results of the descriptive statistical analysis of this study show that the supervision of madrasa heads is in the medium category with a total frequency of 74 people with a percentage of 77.9%, and teacher performance is in the medium category with a total frequency of 73 people with a percentage of 76.8%. The results of inferential statistical analysis show that the value of ttable (7.837> 1.661). With a significance value of 0.05 which indicates H1 is accepted and H0 is rejected. Based on the results of these data it can be concluded that there is a significant influence between the supervision of the madrasah head on the performance of teachers in MTs Negeri throughout Kolaka Regency.